Strategi Pembelajaran Baca Tulis Arab Melayu pada Siswa Madrasah Ibtidaiyah di Kabupaten Aceh Tengah - Muhammad Naufal; Sri Mawaddah (Bayt Al Hikmah: Jurnal Pendidikan dan Pengembangan Masyarakat Islam, 2025)
The urgency of this research lies in addressing the challenge of preserving the Arab-Malay script amid the declining interest of younger generations in learning it, particularly at the elementary education level. This study aims to identify the teaching strategies used by teachers in teaching Arab-Malay literacy at Madrasah Ibtidaiyah in Central Aceh Regency, as well as to examine the obstacles faced, the creativity of the teachers, and the role of cultural environment in the learning process. The subjects of this study include teachers who teach Arab-Malay or similar local content subjects, as well as students in grades IV to VI at several Madrasah Ibtidaiyah in the region. The research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings reveal that teachers implement various innovative strategies, such as the use of visual media, learning through play methods, and the integration of local cultural values to enhance students' interest and understanding of the Arab-Malay script. However, the learning process also encounters challenges, including limited teaching materials, lack of teacher training, and low student motivation. Moreover, support from families and the local community significantly influences the success of the learning process. In conclusion, teacher creativity and synergy between school, family, and local culture are key factors in supporting the effective and sustainable teaching of Arab-Malay literacy.